Analisis Kerusakan Propeller Blade P/N R815505-6 dengan Metode Root Cause Failure Analysis pada Pesawat ATR 72 - Egi Nurfauzi; Lilies Esthi Riyanti; Bhima Shakti Arrafat (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
The propeller blade is a component that is the main source of thrust on the ATR 72 aircraft. Based on data from the Aircraft Flight Maintenance Log (AFML) for the period 2019 – 2021 ATR 72 aircraft, the propeller blade component was damaged causing the need for unscheduled removal which had impact losses to airlines such as delays and aircraft-on-ground (AOG). This study aims to find the root causes of damage to the propeller blade components. Analysis was carried out using the Root-Cause Failure Analysis (RCFA) method using fault tree analysis (FTA) and fishbone diagrams as tools so that factors related to propeller blade damage will be found. The results of analysis using fault tree analysis (FTA) and fishbone found that the root cause of damage to the propeller blade was in the area of ​​the heating element (de-icer) as the top event, while the propeller blade operation, propeller blade maintenance and the ATR 72 aircraft operating environment were the intermediate events